Home page for accesible maths 6 Chapter 6 contents

Style control - access keys in brackets

Font (2 3) - + Letter spacing (4 5) - + Word spacing (6 7) - + Line spacing (8 9) - +

6.22 Example

Example.

Find a particular solution to the equation

(x2-1)dydx+2y=x+1(x^{2}-1)\frac{dy}{dx}+2y=x+1

satisfying y(0)=1y(0)=1.

We have to be slightly careful here, as this equation is not in the form dydx+p(x)y=q(x)\frac{dy}{dx}+p(x)y=q(x). We first divide through by (x2-1)(x^{2}-1) to obtain

dydx+2x2-1y=1x-1.\frac{dy}{dx}+\frac{2}{x^{2}-1}y=\frac{1}{x-1}.

Now the integrating factor is eF(x)e^{F(x)} where F(x)=2dxx2-1F(x)=\int\frac{2\,dx}{x^{2}-1}.